2012
DOI: 10.1016/j.energy.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency in South Africa: A decomposition exercise

Abstract: Improvement of energy efficiency has been accepted as one of the most cost-effective approaches towards sustainable economic development and reduction of the continuously increasing energy consumption internationally. South Africa, being among the developing countries, is not an exception even though historically low energy prices and the lack of appropriate policies have created an energy-intensive economy. This paper examines the factors affecting the trends in energy efficiency in South Africa from 1993 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 28 publications
1
33
0
1
Order By: Relevance
“…The most commonly used were various cointegration techniques (Inglesi, 2010;Ziramba, 2008;Amusa et al 2009). However, there were two studies identified that tried to unfold the factors affecting changes in energy and electricity consumption by using decomposition methods (Inglesi-Lotz and Pouris, 2011;. The overall results showed that changes in the structure of the economy as well as changes in the efficiency that the country uses energy (electricity) play an important role in the trend of energy usage.…”
Section: South African Department Of Energy (Doe)mentioning
confidence: 99%
“…The most commonly used were various cointegration techniques (Inglesi, 2010;Ziramba, 2008;Amusa et al 2009). However, there were two studies identified that tried to unfold the factors affecting changes in energy and electricity consumption by using decomposition methods (Inglesi-Lotz and Pouris, 2011;. The overall results showed that changes in the structure of the economy as well as changes in the efficiency that the country uses energy (electricity) play an important role in the trend of energy usage.…”
Section: South African Department Of Energy (Doe)mentioning
confidence: 99%
“…Further, the industrial sector has been shown to have a high-energy-intensity character [3]. From this it is clear that some industrial firms do not readily adopt EE technologies to help reduce their intensity profile.…”
Section: Introductionmentioning
confidence: 99%
“…[44,77] Energy efficiency GDP/Ec Ec-Total energy consumption [32,36,56,57,60,[63][64][65][66]78] Data sources: Main data sources include the China Statistics Yearbook (2006-2017), the National Bureau of Statistics of The People's Republic of China, and the Wind Database. The reserve and production ratios and production diversity index were derived from the China Statistics Yearbook.…”
Section: Energy Supply Security Index Constructionmentioning
confidence: 99%